2023
DOI: 10.1111/tpj.16070
|View full text |Cite
|
Sign up to set email alerts
|

Going broad and deep: sequencing‐driven insights into plant physiology, evolution, and crop domestication

Abstract: SUMMARY Deep sequencing is a term that has become embedded in the plant genomic literature in recent years and with good reason. A torrent of (largely) high‐quality genomic and transcriptomic data has been collected and most of this has been publicly released. Indeed, almost 1000 plant genomes have been reported (http://www.plabipd.de) and the 2000 Plant Transcriptomes Project has long been completed. The EarthBioGenome project will dwarf even these milestones. That said, massive progress in understanding plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…The articles also differ with regard to the number of genotypes sequenced with many articles providing high-quality sequence of only a single genotype, while others such as that of (Aflitos et al, 2014) reported the sequencing of up to 1000. In keeping with the expansion of the breadth of sequencing (Gui et al, 2022), the pan-genome of bread wheat is reported in a recent resource article (Montenegro et al, 2017;Zhu et al, 2021).…”
Section: Genomes Of Model Species Major Crops and Minor Crops And Pan...mentioning
confidence: 99%
“…The articles also differ with regard to the number of genotypes sequenced with many articles providing high-quality sequence of only a single genotype, while others such as that of (Aflitos et al, 2014) reported the sequencing of up to 1000. In keeping with the expansion of the breadth of sequencing (Gui et al, 2022), the pan-genome of bread wheat is reported in a recent resource article (Montenegro et al, 2017;Zhu et al, 2021).…”
Section: Genomes Of Model Species Major Crops and Minor Crops And Pan...mentioning
confidence: 99%
“…1 ). In parallel, the advent and adoption of techniques that can simultaneously determine the levels of hundreds of metabolites ( Fiehn et al , 2000 ; Alseekh and Fernie, 2018 ) alongside the opportunities afforded by next-generation sequencing ( Purugganan and Jackson, 2021 ; Gui et al , 2023 ) have opened up the possibility of evaluating much broader genetic variance, such as that available in advanced breeding populations ( Alseekh et al , 2021 ; Sharwood et al , 2022 ; Bulut et al , 2023 ) and panels of natural variants ( Fang and Luo, 2019 ). Although such populations have been reviewed extensively elsewhere ( Fernie and Klee, 2011 ; Wijnen and Keurentjes, 2014 ), we will briefly describe their development here since they are highly relevant to the following sections.…”
Section: Single-mutants To Segregating Populations To Genome-wide Ass...mentioning
confidence: 99%
“…Technologies such as nanopore sequencing [45][46][47] and high-throughput phenotyping [48,49] have increased the rate of data collection. The analysis of such data will provide a deeper understanding of plants leading to the generation of new knowledge and new paths to exploitation.…”
Section: Introductionmentioning
confidence: 99%